Animasi 3D Arsitektural Mix Dengan Motion Grafik Sebagai Media Promosi Perumahan Bhumi Nirwana - Muktiana, Adhi Latief; Nurfaizal, Yusmedi (Technomedia Journal, 2022)
The house is the greatest treasure for the family and is the most importantplace to live. In promoting the house, of course, there are many promotional media used, such as print media or electronic media. PT. Anugrah Bumi Sejati is a company engaged in property and home marketing. So far, companies use print media as a medium that has many limitations, such as potential buyers not knowing more information about the details of the house to be purchased. For that, by making 3D animation as a home promotion media at PT. Anugrah Bumi Sejati isexpected to have an impact on increasing sales. This 3D animation is made usinglow poly technique and the resulting output is a 3D animation as a home promotion medium at PT. Anugrah Bumi Sejati which displays the exterior and interior of the house. In accordance with the results obtained by the author because of the need for 3D animation for housing promotion purposes, the author will conduct research that aims to help promote houses that will be made using 3D Modeling low poly and rendered using v-ray and mixed with motion graphics. The result of this design is a house in 3D that can be used as a new medium and innovation for home buyers who want to live in